PENGARUH KAMPANYE #GOJ3K TERHADAP KEPUTUSAN MENGGUNAKAN GOJEK DI TENGAH PANDEMI COVID-19 (Survei Kepada Followers Akun Instagram @gojekindonesia) - Nalda Cloudia, (2021)
This study aims to determine the relationship and find out how much influence the #GOJ3K campaign has on the decision to use Gojek in the midst of the covid-19 pandemic carried out through social media Instagram. The model used in this research is the Ostegaard campaign model. This research was conducted using a quantitative approach, the method used is a survey method with a population of 991,000 followers on the Instagram account @gojekindonesia with a sample of 100 respondents. The technique of analyzing the influence of variable X on variable Y uses regression test and coefficient of determination test so as to obtain the results that there is an influence between variable X on variable Y of 68.1% and the rest is influenced by other factors outside the study. The data testing technique was processed using the SPSS version 20 program. The results showed that the correlation value between the X variable and the Y variable was 0.813 which means that there is a very strong relationship besides that based on the results of the hypothesis test, namely H1 is rejected and Ha is accepted which means that the Campaign Message #GOJ3K affects the decision to use Gojek in the midst of the Covid-19 pandemic.